INDIA AS A NEW CENTER OF GLOBAL INFLUENCE - Sergey Lunev (Сравнительная политика)
Abstract: India confidently entered the community of the leading international powers. Its rapid economic growth is accompanied by increased international activity and modernization of military forces. Meanwhile these successes emerged, despite complicated regional environment. In this situation intensification of the Indian foreign policy contributes to the development of its cooperation with the growing range of partners.